2022
DOI: 10.1111/joes.12533
|View full text |Cite
|
Sign up to set email alerts
|

The impact of professional sports franchises and venues on local economies: A comprehensive survey

Abstract: Local governments routinely subsidize sports stadiums and arenas using the justification that hosting professional franchises produces economic development and social benefits in the community. The prevalence of venue subsidies generated an extensive and vibrant research literature, which spans over 30 years and includes more than 130 studies. We chronicle this body of research from early studies of tangible economic impacts in metropolitan areas, using basic empirical methods, through recent analyses that foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 162 publications
0
18
0
Order By: Relevance
“…There are two broad strands in the sports stadium literature. The first concerns the impact of new stadia on the local economy, for a comprehensive survey see Bradbury et al (2022). The second, which is the subject of this paper, concerns the direct impact of new stadia on the sports business itself, in terms of attendance, prices and revenues.…”
Section: Stadium Effectsmentioning
confidence: 99%
“…There are two broad strands in the sports stadium literature. The first concerns the impact of new stadia on the local economy, for a comprehensive survey see Bradbury et al (2022). The second, which is the subject of this paper, concerns the direct impact of new stadia on the sports business itself, in terms of attendance, prices and revenues.…”
Section: Stadium Effectsmentioning
confidence: 99%
“…The other 15 % of gate revenue is received by the team (row 3) and has no direct effect on the local economy; however, the visitors providing that revenue do spend money on the local economy. Bradbury et al (2023) provide a broad review of recent studies about the effects of teams on the local economy, and conclude that "when positive effects exist, they occur very close to venues, within 1 or 2 miles, and in sectors closely related to sports consumption (e.g., In order to obtain the formula for (4), define x = "gate receipts from visitors" and y = "total spending by visitors," and note that, according to the U.S. Travel Association, x = 0:36y, or y = x=0:36. We want to estimate the gain for the (rest of the) local economy, which is equal to Àx = x 0:36 À x = 0:64 0:36 x; (6) Multiplier assumed equal to 1.5.…”
Section: Attendance and Multiplier Effectsmentioning
confidence: 99%
“…The other 15 % of gate revenue is received by the team (row 3) and has no direct effect on the local economy; however, the visitors providing that revenue do spend money on the local economy. Bradbury et al (2023) provide a broad review of recent studies about the effects of teams on the local economy, and conclude that “when positive effects exist, they occur very close to venues, within 1 or 2 miles, and in sectors closely related to sports consumption (e.g., food and beverage).” 13 For simplicity, and based on an estimate of the U.S. Travel Association for 2018, here we consider that, on average, 36 % of visitors’ sports travel spending goes to sports events. We can use this figure to estimate the total amount spent by visitors in the area and thus also the amount received by other local businesses (row 4).…”
Section: Economic Impact Of An “Average” Professional Sports Teammentioning
confidence: 99%
See 1 more Smart Citation
“…Tu (2005) was the first to uncover a distance-decaying effect, with homes selling for a premium closer to FedEx Field compared to otherwise similar homes a little further away, and a wealth of subsequent research in different contexts with varying methodological approaches have found similarly (Ahlfeldt & Kavetsos, 2014; Ahlfeldt & Maennig, 2010; Chikish et al, 2019; Feng & Humphreys, 2012, 2018; Humphreys & Nowak, 2017; Kavetsos, 2012; Propheter, 2019a). The consistency is surprising in part because the same literature also reaches near consensus that facilities have little to no effect on any other tangible economic outcomes such as jobs, wages, and so forth (Agha & Rascher, 2021; Bradbury et al, 2022; Humphreys, 2019; Matheson, 2019). The amenity theory, however, is not settled, and the literature on facilities’ impact on nearby property prices continues to develop (Propheter, 2020).…”
Section: Facility Property Price Effects and The Golden State Warrior...mentioning
confidence: 99%